Comparing Intradermal (ID) Rabies Vaccination with Conventional IM Regimen on Humoral Response of New Zealand White Rabbits for the Production of Animal-Derived Polyclonal Antibodies - Amina Najam; Rameesha Abid; Hussain Ali; Hamza Hafeez; Amna Arif; Safia Ahmed; Alessandro Di Cerbo; Shakira Ghazanfar (Veterinary Medicine International)
In developing countries, it is imperative to implement cost-effective strategies for animal humoral response development in the production of antiserum. This study compared the effect of immunization regimens on the humoral immune response of New Zealand White (NZW) rabbits (N = 24) using cell culture rabies vaccine (CCRV) through intradermal (ID) and traditional intramuscular (IM) routes. The rabbits were divided into three experimental groups: (a) IPC-R2 with a two-site one-week regimen; (b) TRC-R3 with a two-site twenty-eight-day regimen; and (c) Alternate-R4 with a four-site one-week regimen. These regimens were then compared to the standard IM schedule of five doses of rabies vaccine administered at days 0, 3, 7, 14, and 28 in control group R-1. The results were evaluated at days 14 and 35 postvaccination using rabies-specific Platelia II™ ELISA kit method. The results showed a better response to the ID regimen than the IM route regarding immunogenicity and volume consumption of the vaccine. The three selected ID regimes showed significantly higher mean titer values than the control IM regimen group R-1 (p<0.001). The study aims to explore simple immunization strategies to enhance the RV-specific antibody titers for immunization donor animals. This method would produce polyclonal antibodies and strengthen local production of polyclonal antibodies in Pakistan to deal with vaccine and rabies immunoglobulin (RIG) shortage, thus providing effective postexposure prophylaxis (PEP) for better control of rabies in developing countries.